2010
DOI: 10.1002/hep.23792
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted imbalance of T cells with regulatory function characterizes type 1 autoimmune hepatitis

Abstract: Immunotolerance is maintained by regulatory T cells (Tregs), including CD4 1 CD25 hi , CD8 1 CD28 2 , cd, and CD3 1 CD56 1 [natural killer T (NKT)] cells. CD4 1 CD25 hi cells are impaired in children with autoimmune hepatitis (AIH). Little is known about Tregs in adults with AIH. The aim of this study was to investigate the frequency and function of Treg subsets in adult patients with AIH during periods of active disease and remission. Forty-seven AIH patients (16 with active disease and 31 in remission) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
119
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 45 publications
16
119
2
Order By: Relevance
“…and CD8+ Tregs have been demonstrated by a number of studies on autoimmune diseases (22)(23)(24), transplantation (25) and inflammatory diseases (26). ACAID has also been shown to significantly suppress the induction of experimental uveoretinitis (27).…”
Section: Splenic Cd8+ T Cells From Balble Mice Injected With Cii-spmentioning
confidence: 99%
“…and CD8+ Tregs have been demonstrated by a number of studies on autoimmune diseases (22)(23)(24), transplantation (25) and inflammatory diseases (26). ACAID has also been shown to significantly suppress the induction of experimental uveoretinitis (27).…”
Section: Splenic Cd8+ T Cells From Balble Mice Injected With Cii-spmentioning
confidence: 99%
“…[77] Cytokines and autoimmune hepatitis Autoimmune hepatitis (AIH) is an inflammatory liver disorder, characterized by female preponderance, hypergammaglobulinaemia and interface hepatitis on histology. AIH is associated with impairment of regulatory T-cells, [78] a lymphocyte subset key in maintaining immune-tolerance to autoantigens. [79] Limited data are available for the participation of cytokines in the development of AIH.…”
Section: Structural Organization Of the Liver And Cytokines Potentialmentioning
confidence: 99%
“…Among them, regulatory T cells are particularly important because they participate in the maintenance of immune self-tolerance and homeostasis (25). Moreover, different studies have found a relationship between the impaired number and function of Treg cells and AIH (26,27). It has also been shown that restoration of Treg cell function in subjects with AIH is paralleled by an increase in the expression of Th1/Th2/Th17 transcription factors (28).…”
Section: Controlsmentioning
confidence: 99%